Singlet Oxygen Energy for Enhancing Physiological Function and Athletic Performance - Chia-Feng Hsieh; Chun-Ta Huang; Cheng-Chung Chang; Tun-Pin Hung (Bioengineering, 2025)
A total of 75% of the oxygen humans inhale is exhaled without being utilized. To help organisms better utilize oxygen in exercise training, we designed the singlet oxygen energy generator (SOEG), a device that converts ambient air into energy-rich oxygen. The SOEG comprises an LED light source, a photosensitizer kit, and an air pump. Based on the principle of photosynthesis, the photosensitizer activates oxygen to produce excited-state singlet oxygen under the irradiation of light, which releases about 94 kJ/mol of singlet oxygen energy (SOE) after the relaxation process. After comparing data from 14 volunteers, we found that inhaling SOE during exercise significantly reduces energy consumption during running, decreases oxygen uptake, and improves running efficiency. At the same time, SOE effectively lowers blood lactate levels and improves oxygen utilization, indicating that SOE may enhance endurance and efficiency during exercise.